An Experience Mapping Method for Delayed Understanding in STEM Education - Masaaki Kunigami; Takamasa Kikuchi; Takao Terano (Journal of Systemics, Cybernetics and Informatics)

(untitled)
This study introduces a novel experience-mapping methodology designed to alleviate the challenge of delayed comprehension in education. Education often entails a delayed understanding of its content and value. This comprehension lag often results in discrepancies between learners and educational content, potentially leading to setbacks in the learning process. In response, we present a mapping model that delineates the essential structure of educational content and positioning between the learner and the content. This model serves as a guiding roadmap, enabling learners to navigate the complexities of educational content through a pair of constructed semantic networks. These networks reflect insights from recent brain science and educational experience studies. This study delves into the application of the STEM (Science, Technology, Engineering, Mathematics) education. Furthermore, we discuss the potential of experience mapping within the spheres of curriculum design and faculty development. Through these applications, this research contributes to the development of educational.